Peningkatan Kesadaran Lingkungan Melalui Daur Ulang Minyak Jelantah Dan Edukasi Pemilihan Sampah - Hana Aprilia; M Wildan Salman; Rio Septiantoro; Ayu Firnanda; Siti Alfiyah (CV. ITTC INDONESIA, 2025)
Environmental problems in Gambiran Village persist due to the community's lack of knowledge about managing household waste, particularly used cooking oil and unsorted garbage. Used cooking oil is generally disposed of directly into the ground or waterways, while waste remains mixed without separating organic and inorganic waste. This situation underscores the importance of community service programs to raise environmental awareness. The purpose of this activity is to enhance the awareness, understanding, and skills of community members and students regarding waste management through the utilization of used cooking oil and the early implementation of waste sorting. The method employed is Participatory Action Research, which involves residents, educational institutions, and university students. The program was carried out through workshops on producing aromatherapy candles from used cooking oil, waste-sorting education, and environmental clean-up activities. The results indicate positive changes, including increased community awareness and participation in waste-sorting practices and in utilizing oil waste.